Estimates of the occupational exposure to tenorm in the phosphoric acid production plant in Iran - Fathabadi, N.; Vasheghani Farahani, M.; Moradi, M.; Hadadi, B. (Radiation protection dosimetry, 2012)
Phosphate rock is used world wide for manufacturing phosphoric acid and several chemical fertilisers. It is known that the phosphate rock contains various concentrations of uranium, thorium, radium and their daughters. The subject of this study is the evaluation of the radiation exposure to workers in the phosphoric acid production plant due to technologically enhanced naturally occurring radioactive materials that can result from the presence of naturally occurring radioactive materials in phosphate ores used in the manufacturing of phosphoric acid. Radiation exposure due to direct gamma radiation, dust inhalation and radon gas has been investigated and external and internal doses of exposed workers have been calculated. Natural radioactivity due to (40)K, (226)Ra and (232)Th have been measured in phosphate rock, phosphogypsum, chemical fertilisers and other samples by gamma spectrometry system with a high-purity germanium. The average concentrations of (226)Ra and (40)K observed in the phosphate rock are 760 and 80 Bq kg(-1), respectively. Annual effective dose from external radiation had a mean value of ∼0.673 mSv y(-1). Dust sampling revealed greatest values in the storage area. The annual average effective dose from inhalation of long-lived airborne was 0.113 mSv y(-1). Radon gas concentrations in the processing plant and storage area were found to be of the same value as the background. In this study the estimated annual effective doses to workers were below 1 mSv y(-1).